A comparative study on the value of scenic views between an inland and a coastal city in Korea. (4th May 2019) - Jeong, Taeyun; Park, Sae Woon; Lee, Sunhae
ABSTRACT: This study estimates hedonic house price models for an inland city of Seoul and a coastal city of Pusan using spatial regression with successful bidding price data of court auction during the period from January 2006 to December 2014. Among hedonic attributes such as floor area, building age, total floor level, living floor level, direction of the window of the living room, proximity to natural environment, scenic views and others employed in this study, our main focus is on scenic views. As a result of our empirical analysis, the most preferred view turns out to be a water-related view such as a broad river view in Seoul or an ocean view in Pusan. A mountain view, affecting negatively in a coastal city like Pusan which is adjacent to the beautiful ocean, has positive influence in Seoul, since it is an inland city with no ocean in sight with only a river running across the heart of the city which is surrounded by mountains serving as its boundary. While a building view in Seoul has negative effect on the price, it affects positively in Pusan.